Peran TikTok dalam Kampanye Politik: Strategi Menarik Gen Z di Pemilu 2024 - Marlina, Dwi; Hakim, Lukman (Jurnal Audiens, 2025)
This study analyzes the political communication strategies of Gerindra and PDIP in utilizing TikTok as a campaign platform during Indonesia’s 2024 Presidential Election and its impact on Generation Z engagement. Using a qualitative approach and comparative analysis, this research is grounded in political theories to examine how parties shape public opinion through social media. Data were collected from the official TikTok accounts of both parties during the campaign period using purposive sampling. The analysis focused on content categories, interaction patterns, and engagement levels measured by likes, comments, shares, and party responses to users. The findings reveal that Gerindra adopted a dynamic and entertaining campaign strategy through viral trends and interactive content, while PDIP emphasized a community-based approach to foster voter engagement. Both parties leveraged TikTok features such as short videos, hashtags, and music to reinforce their political messages. This study concludes that TikTok serves as an effective campaign tool in enhancing Generation Z’s political engagement and highlights the growing role of social media in digital political communication strategies.